University learning style model: Bibliometrics and systematic literature review - Laberiano Andrade-Arenas; María Mini Martin Bogdanovich; Domingo Hernández Celis; Katerine Romero Jaico; Gustavo Bernnet Alfaro Peña (Institute of Advanced Engineering and Science, 2023)
The university learning style worldwide was analyzed to obtain a model adapted to Peru, that was complemented in the initial part with the study of the biliometric analysis. In the first steps that were developed, the information search was done in a general way with Scopus. Then specifically adding the Dimensions database, obtaining 59 items from the selection. The Prism statement was used, which allowed it to be developed in the methodology sequentially until the selected articles were obtained. The objective was to carry out a study of the systematic review of the literature (RSL) that allowed analysis by categories such as academic performance, teaching strategy and competencies related to the learning style. Where the data obtained was with the use of VOSviewer and Rstudio. The result obtained was an innovative model that relates the categories with the most relevant models that studied the learning style. As a conclusion, the different learning styles can be adapted to the different study programs and their different courses to plan it from the macrocurricular to the microcurricular, taking into account the strategy and the didactics of teaching, the contribution for the university sector.